Peningkatan Kemampuan Literasi Siswa-Siswi di SDN 54 Aipiri Manokwari Timur Papua Barat - Paradida, Yulia Putri; Andriani, Yeni Yulia; Warami, Hugo; Syufi, Yafed; Arwam, Hendrik; Hussen, Muhammad; Tarigan, Marsten Lihardo; Luhulima, Fiona Djunita Natalia; Leba, Herlyn Winda Wie; Ambarwati, Estiani (Jurnal Pengabdian Arumbai, 2024)
The development of literacy in Indonesia is still low, with minimal interest in reading impacting students' literacy skills. The causes include difficulty in understanding reading and the lack of literacy resources in schools. The School Literacy Movement by the government, including the book donation program, is expected to improve students' literacy and reading comprehension. This program involves counseling, storytelling, and a target of reading one book per month for students. Although challenges such as limited infrastructure exist, cross-sector collaboration and community support are expected to build a strong literacy culture at SDN 54 Aipiri. On September 15, 2023, a community service activity was carried out at SDN 54 Aipiri, East Manokwari, West Papua. Involving students in grades 1-6, lecturers, and Indonesian Literature students, this program aims to improve literacy skills. The stages include planning, implementation, and evaluation to expand student literacy and provide inspiration for similar programs elsewhere. The book donation initiative at SD Negeri 54 Aipiri aims to increase the book collection, stimulate students' interest in reading, and improve the quality of learning. 120 books were collected from various donors, including students, lecturers, and the community. Ongoing efforts involve more contributors. Counseling is carried out at the beginning of each learning session, including storytelling, to increase students' literacy awareness and skills.